Evaluation of phenotypes and genotypes of airborne Fungi during middle eastern dust storms - Yarahmadi, Mohammad (J Environ Health Sci Eng, 2020)
Microbial species such as bacteria and fungi can be transported by dust storms over long distances, and may change the mycobiota in downwind. This study aimed to evaluate phenotypes and genotypes of airborne fungi during the Middle Eastern dust (MED) events and normal days in Khorramabad, Iran. The samples were collected regularly every six days at three locations during April 2018–March 2019, with additional samplings during MED days. For phenotypic analyses, the Petri dishes were incubated at 25 °C for 72–120 h. Molecular identification of fungi was carried out using polymerase chain reaction (PCR). The average (±SD) of total fungal concentration was 460.9 (±493.2) CFU/m(3). The fungi with the highest average concentrations included Cladosporium cladosporioides, Penicillium brevicompactum, and Cladosporium iridis, respectively. The average concentration of fungi during dust days (967.65 CFU/m(3)) was 3.6 times higher than those in normal days (267.10 CFU/m(3)). During normal and dust days, 61 and 45 species were detected, respectively. Aspergillus and Cladosporium spp. were relatively more dominant during normal and dust days, respectively. Eight fungal species were only observed during MED days, including Talaromyces albobiverticillius that was detected for the first time in Iran. Despite air temperature, relative humidity and wind speed were associated to the fungal concentrations. Dust events lead to the changes in the air pollutants composition and mycobiota, identification of new fungi, and elevated fungal concentrations that may extremely affect the public health. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40201-019-00428-0) contains supplementary material, which is available to authorized users.